Lessons learned from piloting decentralized, smart miniature food pantries to mitigate college student food insecurity - John Jones; Lauren Linkous; Lisa Mathews-Ailsworth; Reyna Vazquez-Miller; Elizabeth Chance; Jackie Carter; Isaac Saneda; Youngmi Kim; Leland Waters (Journal of Agriculture, Food Systems, and Community Development, 2025)
Food insecurity on college campuses is a persistent challenge that has recently emerged as significant on a national level. Campus officials across the U.S. are beginning to launch campus food pantries to mitigate food insecurity among their student populations. However, emerging scholarship suggests that many college students may not be aware of their campus food pantry. This reflective essay presents preliminary lessons learned from an ongoing pilot program at Virginia Commonwealth University (VCU) to mitigate student food insecurity. Launched in October 2021, the program deployed 13 miniature food pantries across both VCU campuses. These pantries allowed decentralized, anonymous access to emergency food on a 24-hour, seven-days-a-week basis. The research team developed a partnership with the regional food bank to ensure a stable pipeline of food for the pilot. A combination of service learning and work-study students restocked the pantries weekly, while simultaneously collecting observational data on pantry operations. Wi-Fi enabled door sensors built into the pantry boxes to collect anonymized data when individuals opened a pantry door. The authors reflect on the challenges to implementing the pilot program, with a specific focus on navigating the university’s bureaucracy, information technology issues related to the development of the sensor network, establishing a stable pipeline of food, day-to-day management, and the difficulties of expansion. The paper ends with a number of recommendations. Higher education faculty and staff interested in deploying similar campus mutual food pantry systems may find this reflective essay informative.